Comparison on physicochemical properties of mung bean flour and isolated starch under different level of high static pressure. Issue 6 (25th August 2021) - Liu, Zhenyu; Fu, Yongxia; Zhang, Jing; Shen, Qun
Abstract: Background and objectives: Mung bean has high nutritional value for consumers, but its native form with poor physicochemical properties limited uses for food production. Mung bean flour (MBF) contains starch and nonstarch components including proteins, lipids, and fibers. Nonstarch components possibly cause the physicochemical properties of MBF to be different from those of mung bean starch (MBS). Thus, effect of high‐hydrostatic pressure (HHP) (300, 450, and 600 MPa) processing on the structural, thermal, pasting, and rheological properties of MBF and MBS was investigated. Findings: Results showed that MBF and MBS exhibited various properties under the same HHP treatment. With increasing pressure, the Maltese cross and relative crystallinity of MBS disappeared more significantly than MBF, indicating more severe gelatinization. Furthermore, MBF was seen to have more short‐range ordered structure than MBS. The peak viscosity (PV), trough viscosity (TV), and breakdown viscosity (BV) of MBF were lower than just the MBS only. MBF contained protein, lipid, and fiber, which could compete with starch to absorb water in the food gel systems, thus hindered the swelling and gelatinization of starches. And amylose–lipid complexes were formed in HHP‐treated MBF which could enhance the gel network cross‐linking, with lower tan δ (loss modulus/storage modulus). Conclusions: Nonstarch polymers in MBF might protect starch granules from gelatinization under HHP, obvious differences were observed in the thermal, pasting, and rheological properties between HHP‐treated MBS and MBF, and physicochemical properties were greatly related to structural properties of them. Significance and novelty: Overall, HHP as a nonthermal processing technique has potential to modify legume flour with a range of properties into diverse food products.